DEVELOPMENT OF COGNITIVE GUIDANCE MODEL USING PICTURE STORYBOOK MEDIA TO DEVELOP SOCIAL COGNITION IN CHILDREN AGED 5-6 YEARS AT KYOMOON GRACE KINDERGARTEN - Putri Tania Natalia; Kadek Suranata; Dewi Arum Widhiyanti Metra Putri (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Early Childhood Education (PAUD) plays a crucial role in the early stages of a child's development, both cognitively, emotionally, and socially. Between the ages of 5 and 6, children enter a developmental phase where they begin to differentiate between desirable and undesirable behaviors, as well as understand simple rules, share, and empathize (Sulaiman et al., 2021). Social Cognitive Development is a child's ability to understand, process, and respond to social relationships around them (Ningsih, 2023). In early childhood, this capability encompasses various aspects, such as sharing, empathy, cooperation, and understanding rules. The study employed a quantitative approach with the Single Subject Design (SSD) method, specifically the Multiple Baseline Across Subjects model, consisting of a baseline phase and an intervention phase. The study was conducted at KYOMOON GRACE Kindergarten. The study subjects were 5 children who were most in need of social cognitive development based on initial observations and a pre-test. The subjects were selected based on their age, aged 5 and 6 years, and who needed social cognitive development. Data collection techniques included pre-tests and post-tests, observation rubrics, and interviews. The media used was a picture storybook. Data analysis used quantitative descriptive analysis to assess the feasibility of the picture storybook, practicality testing, and intervention outcomes. The results showed that the picture storybook product received a score of 95%. For the five research subjects, the cognitive guidance model using picture storybooks was considered highly effective, with a percentage of non-overlapping data. The average pre-test to post-test score increased from 56.8 to 114.0. This study also showed that the highest increase occurred in the Sharing/Taking Turns indicator. Thus, the development of a cognitive guidance model using picture storybooks helps develop social cognitive skills in children aged 5-6 years.